Numerical fracture investigation of single-edge notched asphalt concrete beam based on random heterogeneous FEM model. (18th October 2021) - Teng, Guocui; Zheng, Chuanfeng; Chen, Xiangyin; Lan, Xuli; Zhu, Yimo; Shan, Chao
Highlights: A novel algorithmic procedure for random heterogeneous modelling has been proposed. Visualization of the crack propagation path and stress distribution is achieved. Quantitatively analyze the variation of the microcracks characteristics. Shape of microcracks connected in fracture zone is extracted by plug-in written in python. Abstract: A finite element simulation of a single-edge notched beam was performed to investigate the crack characteristics of asphalt concrete during the fracture process at different low temperatures. A novel algorithmic technique was proposed for random heterogeneous modeling considering the aggregate gradation and void of AC-13. The fracture constitutive parameter was calibrated using the Kalman filter algorithm combined with image recognition. Moreover, the reliability of the simulation was verified through a comparison with a physical test. The results indicate that as the temperature decreased, the crack path became more inclined to the vertical centerline at the mid-span, and the proportion of mode I fracture elements to the total sum of mixed mode I-II fracture elements along the crack path decreased. The equinoxes in the macro unfractured zone near the vertical centerline are approximately the demarcation points between the tensile and compressive stresses, and the tensile, shear, and compressive stresses fluctuate nonlinearly in the vertical direction. At the critical fracture state, the tensile stress distribution along the bottom of the beam appears 'M'-shaped and exhibits multiple peaks owing to the existence of heterogeneous structures; the tensile stress reaches the maximum value at 30 ± 3 mm from the two sides to the vertical centerline. The velocity of crack propagation in the mastic increases as the temperature decreases. Cracks incubated inside the aggregate penetrate through the aggregate accompanied with the secondary fissures more rapidly than propagate in mastic. In addition, the connected microcracks appear wedge-shaped in the mastic and fan-shaped in the aggregate.